A Liaden Universe constellation. IV - Lee, Sharon, 1952-; Miller, Steve, 1950 July 31- (Lee, Sharon, 1952- Liaden universe., 2019)
For more than thirty years, the Liaden Universe® novels by Sharon Lee and Steve Miller have captivated readers with their unique blend of action adventure, science fiction, and romance. In addition to twenty-one novels (and counting) Lee and Miller have written dozens of shorter works based in the Liaden Universe®, featuring the strong characterization, detailed world-building, wit, and derring-do that readers of the series adore. This fourth volume collecting Lee and Miller<U+2019>s shorter Liaden Universe® stories features four novelettes, two novellas, and two short stories <U+2013> including the celebrated linked stories, "Block Party" and "Degrees of Separation." Sure to delight longtime fans and newcomers alike, these tales highlight why the nationally best-selling Liaden Universe® novels are treasured by space opera aficionados, with detailed world-building, strong characterizations, compelling romance, and edge-of-the-chair action in stories that range from cosmic to comic.